Edukasi Hidup Sehat Tanpa Rokok pada Remaja - Nel Efni; Tina Yuli Fatmawati (Jurnal Abdimas Kesehatan (JAK), 2023)
The habit of smoking in Indonesia was found to have started since childhood. According to the 2018 Riskesdas, the percentage of smoking behavior in school-age adolescents (age 10-18) was recorded at 9.1 percent, an increase from Riskesdas, which was 7.2 percent. WHO also explained that 30% of the world's population who smoke are teenagers. The purpose of this community service is to increase adolescent knowledge about the dangers of smoking and to change adolescent behavior towards a healthy lifestyle (healthy without smoking). The methods of service applied are lectures, discussions, role plays. Community service activities were carried out from October 2022 to January 2023 with 30 students at SMP N 8 Jambi City. Results obtained. there was an increase in students' knowledge after being given health education about the dangers of smoking. By 93.3%. Parents / families pay more attention to growth and development and pay more attention to their children who have reached their teens, especially avoiding smoking behavior